HUBUNGAN PERSEPSI SISWA TENTANG PARTISIPASI ORANG TUA DENGAN MOTIVASI BELAJAR DI MTs MENAMING KECAMATAN RAMBAH KABUPATEN ROKAN HULU - -, Hardianto (Edu Research, 2013)
The baground of study is less parental involvement and student motivationat MTs Minaming Kecamatan Rambah. The problems of the reasearch are: 1)Students do not focus when the teacher explains the subject, 2) they do theirhomework together in the class, 3) there is assumption that parents ask theirchildren to study as well as they forget their responsibility, 4) there is thedifficulties to get helping from them about how to improve students' progress. Theaims of research is how students' perceptions about parents’ participation, to findout how students' motivation and to determine whether there is a relationshipstudents' perceptions about parental involvement and student motivation or not inMTs Menaming Kecamatan Rambah.